Predicting Factors influencing Islamic Marketing. A research upon emerging Marketing Paradigm.: Predicting Factors influencing Islamic Marketing. A research upon emerging Marketing Paradigm. (KASBIT Business Journal, 2023)
Abstract: Muslims are a large and separate segment. The needs of this segment needs to be catered in accordance with religion of Islam that have guided about all aspects of life. The purpose of this research was to formulate and validated the model of Islamic marketing. A total number of 268 Business graduates were respondent of this research by making use of convince sampling technique with the help of questionnaire designed on five point Likert scale. The model and hypothesis are tested with the help of SEM. Three hypothesis were found to be significant and one is failed to be accepted. Halal aspects, Islamic Philosophy and Muslim consumer behavior are the main identified components of Islamic marketing. This model may use by marketer who want to market their business in an Islamic way.  Keywords: Islamic Marketing, Halal Marketing, Islamic Philosophy of Marketing